Kemampuan Menulis Puisi Ditinjau dari Struktur Fisik dan Batin Puisi - Zathu Restie Utami (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
This quantitative research aims to find out how the poetry writing abilities of class X students are in terms of the physical structure and inner structure of poetry. This research is quantitative research using data collection techniques in the form of performance tests (writing poetry), while the data analysis technique used is descriptive statistics. The research results showed that students' ability to write poetry from the perspective of the physical structure of poetry obtained an average score of 57 with a range of scores from 0 to 59; The inner perspective of poetry received an average score of 64 with a range of scores from 60 to 70. So, overall the ability to write poetry for class X students received an average score of 59 with a range of scores (0-59) in the poor category.